Existential Ennui: Examining the Reciprocal Relationship Between Self-Alienation and Academic Amotivation. Issue 7 (September 2018) - Kim, Jinhyung; Christy, Andrew G.; Schlegel, Rebecca J.; Donnellan, M. Brent; Hicks, Joshua A.
Two studies ( N = 649) examined the association between self-alienation (SA; i.e., feelings of detachment from one's true self ) and academic amotivation (AA; i.e., lack of motivation in the academic domain). Based on classical and contemporary theories, a strong link between alienation and amotivation was predicted. A cross-sectional correlation study (Study 1) found that SA significantly predicted AA controlling for relevant variables (e.g., self-efficacy). A four-wave longitudinal design (Study 2) tested the reciprocal relationship between SA and AA within persons. Contrary to the a priori hypothesis that SA would predict amotivation, the path from AA to SA was more consistent and reliable than the other path. The potential bidirectional links between SA and AA, implications, and future directions are discussed.